Effects of a motivational, individual and locally anchored exercise intervention (MILE) on cardiorespiratory fitness: a community-based randomised controlled trial - Kirstine Høj Obling; Kristian Overgaard; Lise Juul; Helle Terkildsen Maindal (BMC, 2019)
Abstract Background Risk factors for chronic disease, including low cardiorespiratory fitness levels (VO2max), are often present in middle-aged populations. We aimed to evaluate the efficacy of a motivational, individual, and locally anchored physical activity intervention on increasing VO2max in 30-49 year-olds with low VO2max. Methods 232 adult volunteers with low VO2max were randomised to intervention (n = 115) or routine care (n = 117). The intervention included four motivational interviews; six months' free membership to a local sports club; and a GPS-watch/activity monitor for uploading training data to an online platform/community. Routine care was one or two motivational interviews. Inclusion criteria were low VO2max based on the cut off levels: ≤ 39 and ≤ 35 ml O2/kg/min. For 30-39 and 40-49 year-old men respectively and ≤ 33 and ≤ 31 ml O2/kg/min for 30-39 and 40-49 year-old women, respectively. The primary outcome was change in VO2max from baseline to twelve months estimated with a maximal ergometer bicycle test. Secondary outcomes included physical activity, biochemical and anthropometric measures, and health-related quality of life. The primary analyses were based on all available data and sensitivity- and predefined sex analyses were performed. The between-group differences were estimated using independent t-tests and presented with 95% confidence intervals. Results No significant between-group differences in primary or secondary outcomes were found at twelve months' follow-up. The mean VO2max change from baseline in the intervention- and routine care (ml/kg/min) was 3.8 (95% CI: 2.6; 5.0) and 3.4 (95% CI: 1.7; 5.2), respectively. No changes in physical activity were observed. The mean VO2max (ml/kg/min) changes from baseline in the intervention- and routine care group in men were: 5.0 (95% CI: 3.5; 6.4) and 3.5 (95% CI: 1.5; 5.4); and in women: 1.5 (95% CI: -0.1; 3.1) and 3.4 (95% CI: -0.1; 7.8), respectively. Significant differences in VO2max between non-completers (44.2%) and completers were observed, 26.3 (95% CI: 25.1; 27.5) vs 28.2 ml/kg/min (95% CI: 27.1; 29.0; p = 0.02). Sensitivity analyses did not change the main result. Conclusion Offering a multi-component physical activity intervention to 30-49 year-olds with low levels of VO2max had no effect on the change in VO2max from baseline to twelve months compared with routine care. Trial registration ClinicalTrials.gov (no. NCT01801956). Registered 1 March 2013.